Analisis Alih Kode dan Campur Kode Dalam Tayangan Televisi Emak Enah di Trans 7 - Shofia, Marwa; Supendi, Deden Ahmad; Firdaus, Asep (PT. Alahyan Publisher Sukabumi, 2024)
This research uses descriptive qualitative analysis with the subject in this research being a program on the Trans 7 channel, namely the program